Vemurafenib‐Associated Pancreatitis: Case Report. Issue 4 (22nd February 2013) - Muluneh, Benyam; Buie, Larry W.; Collichio, Frances
<x xml:space="preserve">Abstract</x> Vemurafenib is a novel BRAF kinase inhibitor indicated in metastatic melanoma patients with V600E mutation. We report the first case of vemurafenib‐associated pancreatitis. Two weeks after initiation of vemurafenib, a patient presented to the emergency department with severe epigastric pain and a serum lipase of 1544 units/L. Drug‐induced pancreatitis was diagnosed on exclusion of all other potential causes. Vemurafenib was rechallenged at half the daily dose and the patient subsequently developed exacerbated symptoms of pancreatitis after two doses. The strong temporal relationship between drug exposure and toxicity, along with the positive results from a rechallenge study, strongly support a conclusion of causality. To our knowledge, this is the first report of vemurafenib‐induced pancreatitis.